Highly Efficient Leaf Base Protoplast Isolation and Transient Expression Systems for Orchids and Other Important Monocot Crops - Ren, Rui; Gao, Jie; Yin, Dongmei; Li, Kai; Lu, Chuqiao; Ahmad, Sagheer; Wei, Yonglu; Jin, Jianpeng; Zhu, Genfa; Yang, Fengxi (Frontiers in Plant Science, 2021)
Versatile protoplast platforms greatly facilitate the development of modern botany. However, efficient protoplast-based systems are still challenging for numerous horticultural plants and crops. Orchids are globally cultivated ornamental and medicinal monocot plants, but few efficient protoplast isolation and transient expression systems have been developed. In this study, we established a highly efficient orchid protoplast isolation protocol by selecting suitable source materials and optimizing the enzymatic conditions, which required optimal D-mannitol concentrations (0.4–0.6 M) combined with optimal 1.2% cellulose and 0.6% macerozyme, 5 μM of 2-mercaptoethanol and 6 h digestion. Tissue- and organ-specific protoplasts were successfully isolated from young leaves (~3.22 × 106/g fresh weight [FW]), flower pedicels (~5.26 × 106/g FW) and young root tips (~7.66 × 105/g FW) of Cymbidium orchids. This protocol recommends the leaf base tissues (the tender part of young leaves attached to the stem) as better source materials. High yielding viable protoplasts were isolated from the leaf base of Cymbidium (~2.50 × 107 /g FW), Phalaenopsis (1.83 × 107/g FW), Paphiopedilum (1.10 × 107/g FW), Dendrobium (8.21 × 106/g FW), Arundina (3.78 × 106/g FW) orchids, and other economically important monocot crops including maize (Zea mays) (3.25 × 107/g FW) and rice (Oryza sativa) (4.31 × 107/g FW), which showed marked advantages over previous mesophyll protoplast isolation protocols. Leaf base protoplasts of Cymbidium orchids were used for polyethylene glycol (PEG)-mediated transfection, and a transfection efficiency of more than 80% was achieved. This leaf base protoplast system was applied successfully to analyze the CsDELLA-mediated gibberellin signaling in Cymbidium orchids. We investigated the subcellular localization of the CsDELLA-green fluorescent protein fusion and analyzed the role of CsDELLA in the regulation of gibberellin to flowering-related genes via efficient transient overexpression and gene silencing of CsDELLA in Cymbidium protoplasts. This protoplast isolation and transient expression system is the most efficient based on the documented results to date. It can be widely used for cellular and molecular studies in orchids and other economically important monocot crops, especially for those lacking an efficient genetic transformation system in vivo.